InGaN/InGaN multiple-quantum-well grown on InGaN/GaN semi-bulk buffer for blue to cyan emission with improved optical emission and efficiency droop. (April 2017) - Alam, Saiful; Sundaram, Suresh; Elouneg-Jamroz, Miryam; Li, Xin; El Gmili, Youssef; Robin, Ivan Christophe; Voss, Paul L.; Salvestrini, Jean-Paul; Ougazzaden, Abdallah
Abstract: In0.16 Ga0.84 N/In0.05 Ga0.95 N Multiple Quantum Well (MQW) structure grown on a 70 nm thick high quality semi-bulk InGaN buffer layer is reported. Temperature dependent photoluminescence (PL) reveals 67.5% of room temperature Internal Quantum Efficiency (IQE) at an emission peak of ∼455 nm with FWHM of 20 nm. Low temperature PL study shows clear improvement in emission intensity when conventional GaN buffer and GaN barrier are replaced by semi-bulk InGaN buffer in addition with InGaN barrier. Simulation confirms improved IQE and reduced efficiency droop when using semi-bulk as buffer which is attributed to the improved overlapping of electron-hole wave functions due to the reduced internal electric field from counteraction by surface polarization field. This efficiency improvement is very beneficial for high In content green LEDs where the efficiency is limited by polarization induced Quantum Confined Stark Effect (QCSE) for excess indium content. Highlights: In0.16 Ga0.84 N multi-quantum-well grown on high quality In0.05 Ga0.95 N semi-bulk buffer and with In0.05 Ga0.95 N barrier is reported with ∼68% IQE in the blue to cyan emission range. Using semi-bulk InGaN as buffer resulted in more overlap of electron-hole wave functions due to the reduced internal electric field from counteraction by surface polarization field which was explained by simulation. This improved IQE and reduced efficiency droop provides potential extension to green-gap wavelength range emission.